Tradisi Kematian Masyarakat Maunori Etnis Maunori Kabupaten Nagekeo - Febe Fenny Irawati Wanggai; Maksimilianus Doi (Journal on Education, 2025)
This study aimed at finding out the stages and speeches in the death tradition in Maunori Keo Ethnic, Nagekeo Regency. This research employed a qualitative descriptive method. Data were collected adopting interviews and documentation. The results of the study show that in the death tradition, there are several stages of the death tradition with their own speeches, including sodho nderi, toka peti, tee mere, and tona tua tona manu. Derived from these stages, kinship relations can influence the meaning of speech according to status in terms of several aspects, such as position, status, and role, rights and obligations, emotional relationships and communication patterns.